On the 75th Anniversary of Sergei V. Dianov, Doctor of Sciences in Medicine, the Head of the Department of Traumatology and Orthopedics of the Astrakhan State Medical University Ministry of Health of the Russian Federation - Alexey Tarasov (N.N. Priorov Journal of Traumatology and Orthopedics, 2026)
This article presents a brief biographical overview and highlights the scientific achievements of Sergei V. Dianov, Doctor of Sciences in Medicine, Head of the Department of Traumatology and Orthopedics of the Astrakhan State Medical University Ministry of Health of the Russian Federation, along with congratulations on his 75th anniversary. Keywords: Sergei V. Dianov; anniversary; traumatology and orthopedics